Infiltrating lipid-rich macrophage subpopulations identified as a regulator of increasing prostate size in human benign prostatic hyperplasia - Lanman, Nadia Atallah; Meco, Era; Fitchev, Philip; Kolliegbo, Andree K.; Broman, Meaghan M.; Filipovich, Yana; Kothandaraman, Harish; Cresswell, Gregory M.; Talaty, Pooja; Antoniak, Malgorzata; Brumer, Svetlana; Glaser, Alexander P.; et al. (Frontiers in Immunology, 2025)
IntroductionMacrophages exhibit marked phenotypic heterogeneity within and across disease states, with lipid metabolic reprogramming contributing to macrophage activation and heterogeneity. Chronic inflammation has been observed in human benign prostatic hyperplasia (BPH) tissues, however macrophage activation states and their contributions to this hyperplastic disease have not been defined. We postulated that a shift in macrophage phenotypes with increasing prostate size could involve metabolic alterations resulting in prostatic epithelial or stromal hyperplasia.MethodsSingle-cell RNA-seq of CD45+ transition zone leukocytes from 10 large (>90 grams) and 10 small (<40 grams) human prostates was conducted. Macrophage subpopulations were defined using marker genes and evaluated by flow cytometry.ResultsBPH macrophages do not distinctly categorize into M1 and M2 phenotypes. Instead, macrophages with neither polarization signature preferentially accumulate in large versus small prostates. Specifically, macrophage subpopulations with altered lipid metabolism pathways, demarcated by TREM2 and MARCO expression, accumulate with increased prostate volume. TREM2high and MARCOhigh macrophage abundance positively correlates with patient body mass index and urinary symptom scores. TREM2high macrophages have a statistically significant increase in neutral lipid compared to TREM2low macrophages from BPH tissues. Lipid-rich macrophages were observed to localize within the stroma in BPH tissues. In vitro studies indicate that lipid-loaded macrophages increase prostate epithelial and stromal cell proliferation compared to control macrophages. DiscussionThese data define two new BPH immune subpopulations, TREM2high and MARCOhigh macrophages, and suggest that lipid-rich macrophages may exacerbate lower urinary tract symptoms in patients with large prostates. Further investigation is needed to evaluate the therapeutic benefit of targeting these cells in BPH.